Observation of the Lambda(0)(b) -> J/psi Lambda phi decay in proton-proton collisions at root s=13 TeV - (:unkn) unknown (ELSEVIER, 2020)
The observation of the Lambda(0)(b) -> J/psi Lambda phi decay is reported using proton-proton collision data collected at root s = 13TeV by the CMS experiment at the LHC in 2018, corresponding to an integrated luminosity of 60fb(-1). The ratio of the branching fractions B(Lambda(0)(b) -> J/psi Lambda phi)/B(Lambda(0)(b) > psi(2S)Lambda) is measured to be (8.26 +/- 0.90 (stat) +/- 0.68 (syst) +/- 0.11 (B)) x 10(-2), where the first uncertainty is statistical, the second is systematic, and the last uncertainty reflects the uncertainties in the world-average branching fractions of phi and psi(2S) decays to the reconstructed final states. (C) 2020 The Author. Published by Elsevier B.V.
Keywords: CMS; b physics; Heavy-flavor spectroscopy; Computing; RATIO